PENGGUNAAN BERBAGAI JENIS BAHAN AMELIORAN TERHADAP SIFAT KIMIA BAHAN TANAH GAMBUT HEMIK - Zuraida Zuraida (Jurnal Floratek, 2013)
ABSTRACT The study was aimed at determining kinds of ameliorants that increase fertility on Hemic Peats Soil.  The experiment was arranged in a completely randomized design (CRD) with 6 treatments and 4 replications.  The result showed that the ameliorants increased pH (H2O), exchangeable cations (K, Na, Ca, Mg) and base saturation.  Sawdust had the highest ability to increase base saturation, K, and Na.  Lime had the highest ability to increase pH (H2O), Ca, and Mg.  Sawdust increased fertility hemic peats soil better than lime.